PERBANDINGAN CAIRAN FIKSASI BOUIN DENGAN BUFFER FORMALIN TERHADAP HEPAR TIKUS PUTIH - Winny Yohana (Dentistry Faculty, 2017)
Histopathological examination plays an important role in assisting the diagnosis of disease. One indispensable ingredient is a liquid fixation. fixation is a critical step in the preparation of histological section by which body tissue immersed in fixation liquid and preserved from decay thereby preventing autolysis and putrefaction. The aim of this study is to determine the better fixation in between bouin liquid and buffer formalin. The study was an experimental laboratory of two rats. A rat is injected fluids Bouin, others injected buffer formalin. The rats liver is taken and immersed into a fluid according to the injection of a liquid fixation. The rats liver was histologically prepared with hematoxylin eosin staining. The assessment by microscopically examination at 450X magnification. As an indicator seen from the changes in the nucleus of the cell, if there is a cell necrosis (bad) and normal cells (good). The study result shows that Bouin liquid got more normal cells (84.61%), while buffer formalin (38.46%). In conclusion, bouin liquid better than buffer formalinKeywords: fixation, liquid bouin, buffer formalin